Italian Women
A group of 10 Italian women; from left to right: Unknown Cantando, Rose Albanese Antuzzi, Teresa Massa Carozza, Unknown Cantando, Mary Cantando; Unknown, Jenny Casetta, Emma Casetta, Unknown, and Louise Massa Albanese.